MATURIDIYAH: KELAHIRAN DAN PERKEMBANGANNYA - Hamka, Hamka (State Institute of Islamic Studies (IAIN) Palu, 2007)
In discourse of theological thought, the Matturidite and the Asy’arite popularly known as Ahl al-Sunnah wal al-Jama’ah, are two schools of Islamic theology that tried to take the middle path between the conservative theological thought and the rational theological thought. However, in its method of theology, the Matturidite put a greater proportion in the use of reason compared to what the Asy’arite had done. As a result, in some of its theological thoughts, the later tended to be close to the Mu’tazilite rational theology. Social setting of the rise of this school had undoubtedly given a contribution to form its methodological style.Kata Kunci : Maturidiyah, Asy’ariah, Ahl al-Sunnah wa al-Jama’ah, naql, ra’yu